Tamanho de amostra para mosca-branca em soja - Oliveira, Lucas Boeni de (2023)
The whitefly, Bemisia tabaci (Hemiptera: Aleyrodidae), is one of the main pest insects that infest soybean crops. It causes damage through plant sap-sucking, toxin injection, virus transmission, and secretion of a sugar-rich substance that promotes the development of sooty mold. The primary method of controlling the insect is the use of chemical insecticides. Therefore, it is essential to have knowledge of the whitefly population density in the area to determine the need and timing of application. To estimate the population density of the insect pest it is necessary to know the sample size, which is the number of soybean leaflets that should be evaluated. Therefore, the aim of this study was to establish the sample size (number of leaflets) for estimating the mean population density of nymphs and adults of the whitefly in soybean. Twentythree treatments comprising insecticides for whitefly control were evaluated in experiments conducted over two agricultural years, with soybean planting dates on December 11, 2020 (first experiment), and December 17, 2021 (second experiment), with evaluations beginning at the reproductive stages R5.4 and R5.2, respectively. The evaluations were carried out on nine dates in the first experiment and on eight dates in the second experiment. In each experiment, treatment, and date of nymph population assessment, the central leaflet from the middle third of 20 plants per plot (one leaflet per plant) was collected, and the number of nymphs was counted in the laboratory. To assess the adult stage of the whitefly, a visual count was performed in the field on the central leaflet of the upper third of 20 plants per plot (one leaflet per plant). Measures of central tendency and variability were calculated, and normality was verified. The sample size (number of leaflets) was determined based on the Student’s t-distribution. The mean population density of whiteflies was 22.1 nymphs per leaflet and 5.7 adults per leaflet in the first experiment, and 3.0 nymphs per leaflet and 1.9 adults per leaflet in the second experiment. The sample size (number of leaflets) for estimating the mean population density of whitefly nymphs in soybean is 47 leaflets in scenarios of high infestation (22.1 nymphs per leaflet) and 126 leaflets in scenarios of low infestation (3.0 nymphs per leaflet), with an estimation error of 30% of the mean and a 95% confidence level. Regarding the adult stage of whiteflies, for both low infestation scenarios near the control threshold (1.9 adults per leaflet) and scenarios with higher whitefly populations (5.7 adults per leaflet), the sample size is 82 leaflets, with an estimation error of 30% of the mean and a 95% confidence level.